Effect of Alkaline Degumming on Structure and Properties of Lotus Fibers at Different Growth Period. Issue 1 (March 2015) - Li, Fengyan; Fu, Hongjun
Lotus fibers are pulled from different period of lotus root. Alkaline was used as degumming agent to remove non-cellulose impurities of lotus fibers. Environmental scanning electron microscopy (ESEM), X-ray diffraction (XRD) and FTIR were used to characterize surface morphology and microscopic structure of lotus fibers before and after degumming. The effect of alkaline degumming on tensile properties of lotus fibers is investigated. The results show that impurities remove, hydrogen bond rupture, and crystallinity of partly armorphous chain occur during alkaline degumming. All of these changes play roles in influencing fiber tensile breaking force and elongation at break.